1996
DOI: 10.1111/j.1399-3054.1996.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of the ascorbate‐glutathione cycle in aged sunflower seeds

Abstract: The function of the ascorbate‐glutathione (AsA/GSH) cycle was analyzed in seeds of sunflower (Helianthus annuus L. cv. Peredovik) subjected to accelerated ageing at 43°C and 75% relative humidity for 1 to 11 days. The study was performed using dry seeds and seeds hydrated by imbibition in distilled water for 4 h at 25 °C. Lipid peroxidation was also determined by measuring the malondialdehyde (MDA) level. As the ageing period increased, a progressive loss of seed viability became increasingly evident. Even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
5
15
1
Order By: Relevance
“…In general, dry seeds of the orthodox category lack ASA. This was confirmed, for example, in Vicia faba (Arrigoni et al, 1992), Heliantus annuus (De Paula et al, 1996), Pinus pinea, and Avena sativa (Tommasi et al, 1999). Our research showed that ASA is present in dry beech seeds, and this seems to support their intermediate character.…”
Section: Article In Presssupporting
confidence: 84%
See 2 more Smart Citations
“…In general, dry seeds of the orthodox category lack ASA. This was confirmed, for example, in Vicia faba (Arrigoni et al, 1992), Heliantus annuus (De Paula et al, 1996), Pinus pinea, and Avena sativa (Tommasi et al, 1999). Our research showed that ASA is present in dry beech seeds, and this seems to support their intermediate character.…”
Section: Article In Presssupporting
confidence: 84%
“…It is characteristic of beech seeds to contain much more GSSG (oxidized form of glutathione) than GSH (reduced form). Such a strong domination of GSSG has not been observed in seeds of other species, such as H. annuus (De Paula et al, 1996) and Citrullus vulgaris (Hsu and Sung, 1997). Such a shift in redox status may decrease the concentration of -SH groups in cells (Alscher, 1989;Kranner and Grill, 1993).…”
Section: Article In Pressmentioning
confidence: 86%
See 1 more Smart Citation
“…Different responses among different varieties for the considered traits may be due to genetical differences in varieties which agreed with the findings of Armin et al (2010) who found different responses among the watermelon varieties due to priming treatments Numbers of primary and secondary branches per plant were not significantly affected by seed priming. This finding is in agreeable with the findings of Paula et al (1996) who recorded that mustard seed treated with 1% of KH 2 PO 4 did not show significant difference for number of branches per plant. However, Manigopa et al (2007) reported that seed priming brought considerable increase in lateral branches (primary and /or secondary) per plant in chickpea.…”
Section: Primary and Secondary Branches Per Plantsupporting
confidence: 83%
“…In addition, it has been reported that at chilling acclimation at 0°C for 72 h, the GSH content in strawberry leaves reached the maximal values and it then decreased, but it was significantly higher than the control . de Paula et al (1996) revealed that GSH could inhibit the senescence of sunflower seeds and the AsA-GSH cycle is the major detoxifying mechanism in both dry and imbibed sunflower seeds. However, Devarshi et al (2006) thought that there were no significant changes in the GSH content during drought acclimation, but the GSH/GSSG ratio decreased significantly.…”
Section: Ghsmentioning
confidence: 99%